Santiago de Chile - eine fragmentierte Stadt? Eine faktorenanalytische Untersuchung der Stadtstruktur in 2002 im Vergleich zu 1970 - Bähr, Jürgen; Meyer-Kriesten, Kerstin (ERDKUNDE, 2007)
This article attempts to verify the thesis of the fragmentation of the Latin American city, using the example of Greater Santiago de Chile. The methods used are factorial analyses and posterior grouping procedures. Concerning the resident population, this paper examines to what extent the great differences of socio-economic spaces – rich city vs. poor city – are replaced by insular microstructures. The analysis is based on the 2002 census data for the 394 districts of Greater Santiago. The results of the factorial analysis are compared with an earlier analysis using the 1970 census data. In general, almost no change of the structure can be established between 1970 and 2002. Taking all five extracted factors, the explanatory percentages decreased only slightly from 87.3% (1970) to 83.9% (2002). Furthermore, in both years the “socio-economic status” and “life cycle/age structure” can be interpreted as the two most important factors. Both basic dimensions are complemented by one or more factors. These circumstances are considered in the subsequent cluster analysis using the Ward-method. The results support the thesis of a decline of large scale and an increase in small scale segregation. There is only one exception from this pattern. The exclusive Eastern sector of the city remains very homogeneous, despite significant changes of the built environment through the development of gated communities, both of single-family detached houses and apartment buildings. On the contrary, the middle class sectors – clearly identifiable in 1970 – have continuously disintegrated. Today, higher and middle-class areas can be found all over Santiago, often protected by fences and access control systems. In many occasions they have direct borders with lower class neighbourhoods. The clear spatial pattern of 1970, characterised by districts that could be distinguished by social and demographic indicators, has been replaced by a more complex structure consisting of many insular elements. This process of fragmentation is predominantly driven by the middle and higher classes.